Methodology Of Teaching Phrases - Tajiyeva Zukhra Kamalbayevna (Periodica Journal, 2024)
Students preparing for careers in the dairy food industries need opportunities to develop interpersonal, computer, problem solving, and communication skills as well as technical competency in dairy foods.
Keywords: education; dairy foods; students